Active case finding for carbapenemase-producing Enterobacteriaceae in a teaching hospital: prevalence and risk factors for colonization. Issue 2 (October 2016) - Poole, K.; George, R.; Decraene, V.; Shankar, K.; Cawthorne, J.; Savage, N.; Welfare, W.; Dodgson, A.
Summary: Background: Over the past decade, the prevalence of carbapenemase-producing Enterobacteriaceae (CPE) has increased. Whilst basic infection prevention and control practices reduce the risk of transmission, cases of unrecognized carriage pose a potential risk of transmission. Aim: To estimate the prevalence of CPE and explore risk factors associated with colonization within a large teaching hospital with an established CPE outbreak. Methods: All inpatients that had not previously tested positive for CPE were offered testing. Demographic and hospital episode data were also collected, together with antibiotic and proton pump inhibitor (PPI) use in the preceding 24 h. Findings: This study identified 70 CPE-positive cases (26 newly identified and 44 previously known) and 592 CPE-negative cases, giving a combined prevalence of 11% [95% confidence interval (CI) 8–13]. Medication (antibiotic and PPI use), previous admission, ethnicity and length of stay were assessed as risk factors for colonization, and none were found to be independently associated with CPE colonization. Using logistic regression, age [odds ratio (OR) 1.03, 95% CI 1.01–1.07] and antibiotic use (OR 2.55, 95% CI 1.08-6.03) were the only risk factors significantly associated with CPE colonization. Conclusion: This study has added to the evidence base by estimating the prevalence of CPE among inpatients in an acute hospital with an established CPE outbreak. A case-finding exercise was feasible and identified a number of new cases. Despite a small sample size, increasing age and prescription of an antibiotic on the day of testing were significantly associated with CPE colonization.